Financial Feasibility Analysis of Red Chili Pepper Seedling at Karanganyar, Poncokusumo, Malang - Widyastuti, Dyah Erni; Ibrahim, Jabal Tarik; Winaya, Aris; Sukorini, Henik (Universitas Lampung, 2019)
This research aims to analyse financial feasibility of red chili peppers (Capsicum annum L.) seedling business conducted at Karanganyar, Poncokusumo, Malang. The respondents were farmers who breed red chili peppers and the data collected from March to April 2018. The primary data was collected through interviews based on structure questionnaire to obtain information from selected farmers in the study area. The qualitative study is utilized to analyse the financial feasibility based from Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit-Cost Ratio (BCR), and Payback Period (PP). This study findings showed a positive NPV (IDR 15403419), IRR is 23.19%, Gross B/C is 1.05, Nett B/C is 1.13, BCR > 1 (1.05), and PP as 19 months. Despite the costly investment and development, the red chili peppers seedling business is financially feasible